Integrated model of civilisational development an Islamic perspective = Model bersepadu pembangunan sivil satu perspektif Islam - Abdelaziz, Berghout (IIUM Press, International Islamic University Malaysia, 2017)
This article provides an Islamic framework for the study of development and civ-ilization. It proposes an integrated model for balanced development. As such, it ad-dresses the following points: the concept of civilization and civilizational development from an Islamic perspective, mapping the civilizational model for balanced develop-ment and reviving the civilizational vision of Islam as a pre-condition for the revival of the Ummah. In the discussion, leading role of the Islamic view of development and civi-lisation in the progress of society is highlighted; and urgency of a contemporary under-standing of Islam that envisions it as a project for a civilisation of creativity, balance, justice, peace and progress is explained. The methodology applied therein represents analysis of views. The findings show the need for an integrated Islamic model of civili-zational development. The main peculiarities of this model are: value loaded, balanced, comprehensiveness and flexible.